2017
DOI: 10.21037/jtd.2017.09.93
|View full text |Cite
|
Sign up to set email alerts
|

Are beta blockers still necessary for all survivors of acute myocardial infarction?

Abstract: . Comment on: Dondo TB, Hall M, West RM, et al. β-blockers and mortality after acute myocardial infarction in patients without heart failure or ventricular dysfunction. J Am Coll

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…According to the AHA/ACC guidelines, treatment with beta-blockers should be initiated early for patients without contraindications and continued unless adverse effects are observed during the early convalescent phase of ST elevation myocardial infarction (STEMI) [21]. Daisaku et al reported that beta-blocker treatment is still effective in the long-term outcomes of STEMI survivors without LV systolic dysfunction for secondary prevention after AMI [22]. The benefits of ACEI mainly appeared in higher-risk subgroups, but the survival benefit for patients in low-risk subgroups without these features is unclear [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…According to the AHA/ACC guidelines, treatment with beta-blockers should be initiated early for patients without contraindications and continued unless adverse effects are observed during the early convalescent phase of ST elevation myocardial infarction (STEMI) [21]. Daisaku et al reported that beta-blocker treatment is still effective in the long-term outcomes of STEMI survivors without LV systolic dysfunction for secondary prevention after AMI [22]. The benefits of ACEI mainly appeared in higher-risk subgroups, but the survival benefit for patients in low-risk subgroups without these features is unclear [23,24].…”
Section: Discussionmentioning
confidence: 99%